2023
DOI: 10.1039/d2lc00605g
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes and shear stress each alter the shape of a self-assembled vascular network

Abstract: Blood vessel morphology is dictated by mechanical and biochemical cues. Among these, flow-induced shear stress and pericytes have been studied using an on-chip vascular network, for understanding the relationship between...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
(90 reference statements)
1
5
0
Order By: Relevance
“…These findings are consistent with recently published data demonstrating a higher number of vascular sprouts to occur at locations of low shear stress in self‐organized capillary networks in PDMS chips. [ 43 ] These findings also demonstrate the potential of our system for modeling complex events in cancer biology in vitro at the mesoscopic scale.…”
Section: Resultsmentioning
confidence: 59%
“…These findings are consistent with recently published data demonstrating a higher number of vascular sprouts to occur at locations of low shear stress in self‐organized capillary networks in PDMS chips. [ 43 ] These findings also demonstrate the potential of our system for modeling complex events in cancer biology in vitro at the mesoscopic scale.…”
Section: Resultsmentioning
confidence: 59%
“…Pericytes exist around microvessels and play a role in regulating blood flow and angiogenesis. 20 , 21 , 43 We for the first time reported the presence of pericyte in human IA tissue. Pericytes were marked by ABCC9 and KCNJ8 and uniquely expressed HIGD1B (Pct.1=79.5%, Pct.2=1.9%, log 2 FC=1.63) (Figure 1B ), in line with previous findings.…”
Section: Resultsmentioning
confidence: 89%
“… 45 We found that endothelial cells and pericytes interacted through PDGFB‐PDGFRB and TGFB1/3‐TGFBR2 pathways (Figure S2D through S2F ), corroborating the role of pericytes in neovascularization and sprouting. 43 , 46 …”
Section: Resultsmentioning
confidence: 99%
“…4D and E), which is in accordance with recent studies on vessels formed only by HUVECs and pericytes. 31,53 Culturing microvascular networks with a 1 : 1 to 1 : 2 PC-to-EC ratio resulted in very small diameters and the networks were not perfusable anymore. As expected, collagen IV immunostaining also revealed increased deposition of the ECM protein in the basal lamina surrounding the microvessels with higher PC ratios (Fig.…”
Section: Resultsmentioning
confidence: 99%